Innovative classification of technology foresight methods - Magruk, Andrzej (Technological and Economic Development of Economy, 2011)
Since the end of the twentieth century there is a noticeable worldwide paradigm shift in future studies which are so far based mainly on statistical methods. The development of a social, not only a strictly scientific vision of the future has become crucial. It appears that the biggest role in this context played technology foresight programs (whose origins go back even to the 70's), integrating traditional methods of forecasting as well as those derived from the social sciences, economics, management science, etc. The paper presents a rich collection of foresight methods identified by the author, a general outline and characteristics of various types of methods, and an innovative classification of technology foresight research methods. Because of the huge complexity of the approach to technological foresight and its further evolution, the ability to classify and identify the typology of methods may be necessary for an orderly and rational way of structuring foresight projects.Article in English.Nauja technologijų prognozavimo metodų klasifikacijaSantrauka. Nuo XX a. pabaigos visame pasaulyje ateities studijos daugiausia rėmėsi statistiniais metodais. Svarbi tapo socialinės raidos ne tik griežtai mokslinė ateities vizija. Didelis vaidmuo čia atiteko technologijų prognozavimo metodams (jų ištakos siekia aštuntąjį dešimtmetį), integruojantiems tradicinius prognozavimo metodus ir metodus, pasiskolintus iš socialinių, ekonomikos, vadybos ir kitų mokslų. Autorius pateikia ilgą prognozavimo metodų sąrašą, bendrus jų bruožus ir charakteristikas, taip pat siūlo novatorišką technologijų prognozavimo metodų klasifikaciją. Prognozavimo metodai tampa vis sudėtingesni, jie evoliucionuoja, todėl metodų klasifikacija ir tipologija gali praversti struktūrizuojant prognozes.Reikšminiai žodžiai: technologijų prognozavimas, mokslinių tyrimų metodologija, klasterinė analizė, klasifikavimas, tipologija.First published online 18 Jan 2012